Had Kifayah Zakah and Adequacy of Income Redistribution: A Proposal Framework - Bayu Taufiq Possumah (Center of Strategic Studies (PUSKAS) BAZNAS, 2016)
Social security systems traditionally serve a dual purpose: they maintain acquired living standards in the event of the materialization of social risks and combat poverty by guaranteeing adequate minimum income. In this paper we consider Zakat as an important mechanism that strengthens the economy of the entire society by providing Had kifayah as a way to redistribute income. Zakat is also a source of social security to the community, especially to those under inadequate living standards. Had Kifayah Zakat can work as a minimum standard to manage redistribution of income, thereby reducing poverty and balancing economic growth in our society. Keywords: Had Kifayah; Zakat; Social Security; Income redistribution; adequacy